Influence of Introverted and Extroverted Personalities on English Learning Interaction for Elementary School Students - Mustoip, Sofyan; Al Ghozali, Muhammad Iqbal; Fadhlullah, Muhammad Ziyad Fakhri; Assenhaji, Salih Abdulrahman Yousuf (Elsya : Journal of English Language Studies, 2024)
This study examines how introverted and extroverted personalities impact the interaction of learning English at the elementary school level in Indonesia. By using a quantitative method approach through surveys, this research seeks to understand how students' personality traits affect their involvement in learning English. 300 fifth grade public elementary school students in Cirebon City were given a personality assessment questionnaire to identify introverted and extroverted students. Information about students' English learning interactions was collected through observation and self-report measurements. Data analysis used to analyze survey data using multiple linear regression assisted by SmartPLS version 3 includes the use of descriptive statistics, Outer Model Testing and Inner Model Testing. The study revealed that introvert students tend to experience higher levels of anxiety and prefer solitary learning, while extrovert students show more enthusiasm and prefer group activities in English learning interactions. Introverted and extroverted students face challenges in their language learning, such as expressing themselves and finding opportunities to practice. This finding has important implications for English language education in Indonesian primary schools. Educators can use these results to tailor instructional approaches and create inclusive learning environments that meet the diverse needs of introverted and extroverted students. Understanding the influence of personality on language learning interactions can also lead to strategies that enhance student engagement and facilitate effective language acquisition. In conclusion, this study highlights the influence of introverted and extroverted personalities on the interaction of learning English in Indonesian elementary schools. These findings contribute to the teaching of English that teachers should give different treatment to students considering that students have introverted and extroverted personalities.